Persepsi Orang Tua Tentang Pembelajaran Calistung Bagi Anak Usia Dini Di RA Quhas Kindergarten Kota Jambi - Rosyadi, Akhmad Fikri; Fachrunnisa, Rizki; Sofyan, Hendra (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2024)
The aim of this study is to describe parents' perceptions of calistung learning (reading, writing, and arithmetic) for early childhood. This research type is descriptive research with a quantitative approach. Research data was obtained from closed questionnaires by distributing questionnaires to respondents via a Google form. The study employed nonprobability/nonrandom sampling, with 45 parents of children serving as respondents. The average indicator of parents' perceptions of reading comprehension for early childhood is 35.28 %, which falls into the "deficient" category, the average indicator of parents' perception of writing comprehension for early childhood, which falls into the "deficient" category, and the average indicator of parents' perceptions of numeracy comprehension for early childhood, which falls into the "deficient" category.